Comparison of Nutrient Content and Daily Milk Production in Dairy Cows Fed Cipro Plus and Setia Feed Concentrates in KPSP Setia Kawan - Alverina, Aura; Dapawole, Reni Ratni; Rahma, A'idah Attha Saniyah (Universitas Andalas, 2025)
This study aimed to compare the nutrient content and daily milk production of dairy cows fed two types of concentrates: Cipro Plus and Setia Feed. The research was conducted at KPSP Setia Kawan, Pasuruan, using 8 lactating dairy cows divided into two treatment groups. The first group was given Cipro Plus concentrate, and the second group was given Setia Feed. Analysis of the concentrate's nutrient content was performed proximately, while milk production was measured daily for four weeks of observation. The results showed a significant difference (p < 0.05) in the crude protein parameter between the two feed types, specifically 19.09% ± 0.45 for Cipro Plus compared to 16.79% ± 0.25 for Setia Feed. There were no significant differences in moisture content, ash content, crude fat, and crude fiber between the two feed types (p > 0.05). However, Setia Feed tended to have higher crude fat and lower crude fiber content compared to Cipro Plus. Daily milk production of cows fed Setia Feed was also significantly higher (9.1 ± 0.3 liters) compared to those fed Cipro Plus (8.3 ± 0.2 liters). These results indicate that Setia Feed concentrate is superior in increasing the milk productivity of dairy cows and is recommended for use in smallholder farms.